High-Performance Voltammetric Aptasensing Platform for Ultrasensitive Detection of Bisphenol A as an Environmental Pollutant - Hassani, Shokoufeh; Rezaei Akmal, Milad; Salek Maghsoudi, Armin; Rahmani, Soheila; Vakhshiteh, Faezeh; Norouzi, Parviz; Ganjali, Mohammad Reza; Abdollahi, Mohammad (Frontiers in Bioengineering and Biotechnology, 2020)
Bisphenol A (BPA) as a pervasive endocrine-disrupting compound (EDC) has been shown to cause multiple detrimental effects including cardiovascular disorders, pregnancy complications, obesity, glucose metabolism disorders, and reproductive toxicity even at a concentration as low as tolerable daily intake (TDI) (4 μg/kg/day). In the present study, a novel ultra-sensitive, electrochemical aptasensor was designed using a screen-printed carbon electrode (SPCE) modified by gold nanoparticles (Au NPs) conjugated to thiolated aptamers for accurate determination of BPA in biological, industrial and environmental samples. In order to characterize the electrochemical properties of the aptasensor, cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS) were implemented. Detection of BPA was also performed through differential pulse voltammetry (DPV) in [Fe(CN)6]3-/4- electrolyte solution. Under optimum condition, the present electrochemical aptasensor demonstrated an outstanding linear response in the concentration range of 1 pM to 10 nM with a remarkably low limit of detection of 0.113 pM. Due to the superb affinity between anti-BPA aptamers and BPA molecules, the designed aptasensor did not show any significant interaction with other analytes in real samples. Also, fabricated biosensor remained perfectly stable in long-term storage. The analytical results of the fabricated aptasensor are well compatible with those obtained by the ELISA method, indicating the trustworthiness and good accuracy of the application of aptasensor in real samples. Overall, the proposed aptasensor would be a credible and economical method of precise, reproducible, and highly selective detection of minimum levels of BPA in food containers and clinical samples. This would be a promising strategy to enhance the safety of food products and reduce the risk of BPA daily exposure.